Some stability tests for switched descriptor systems. (August 2019) - Sajja, Shravan; Corless, Martin; Zeheb, Ezra; Shorten, Robert
Abstract: In this paper we first derive some general Lyapunov based stability conditions for switched linear descriptor systems and illustrate them with a simple mechanical system. Next we develop simple conditions for specific classes of systems. In particular, we consider the important case when switching between a standard system and an index one descriptor system, and systems where switching occurs between an index one and an index two descriptor system. Examples are given to illustrate these results.